Placement effects of inertial measurement units on contact identification in wheelchair racing. Issue 1 (2nd January 2021) - Lewis, Amy R.; Haydon, David S.; Phillips, Elissa J.; Grimshaw, Paul N.; Pinder, Ross A.; Winter, Joseph; Robertson, William S. P.; Portus, Marc R.
ABSTRACT: Inertial measurement units (IMUs) provide a practical solution for attaining key performance data for wheelchair sports. The effects of IMU placement position on the identification of propulsion characteristics are unknown. The aim of this study was to determine the variability in the reliability of cycle time measurements (time between hand contacts) across IMU locations on the chair frame (axle housings), and wheels (axle, push rim, outer rim), on both the left and right sides ( n  = 8). Contacts were defined by spikes in the resultant acceleration data, corresponding to impact between the hands and push rim, and verified against motion capture. Five elite wheelchair racing athletes propelled at racing speeds on a treadmill. Excellent inter-rater Intraclass Correlation Coefficient values indicated high reliability and repeatability for both motion capture and IMU signal analysis approaches ( R  = 0.997, p  < 0.001 and R  = 0.990, p  < 0.001, respectively). The best results were (as determined by the best between method agreement) were observed for IMUs located on the frame. Detection reliability was positively associated with signal-to-noise ratio of the acceleration data. The IMU assessment approach facilitates an automated processing capability, which is an improvement to the currently used video analysis.